P-223 The Self-management Transition Enhancement Program (STEP): Study Design and Preliminary Findings. (February 2017) - Gray, Wendy; Morgan, Pamela; Holbrook, Erin; Rosen, Michael; Yacyshyn, Bruce; Wise, Caroline; Wagoner, Scott; Schaefer, Megan; Saeed, Shehzad; Denson, Lee; Mackner, Laura; Maddux, Michele; et al.
Abstract : Background: Improving the transition from pediatric to adult IBD care continues to be an important clinical care issue yet data demonstrating the efficacy of existing transition programs are limited. We present an overview of our ongoing intervention pilot feasibility/acceptability trial, the Self-Management Transition Enhancement Program (STEP), along with preliminary data. Methods: Using Intervention Mapping, STEP was systematically developed over 2 years. The first year focused on conducting a needs assessment with pediatric and adult providers as well as pre- and post-transfer patients and parents. The second year focused on co-developing the intervention with input from an Advisory Board comprised of pre- and post-transfer patients and parents, and pediatric and adult providers. The third year of this study is a pilot trial of our intervention. STEP is comprised of one group session followed by 4 one-on-one monthly telehealth-based coaching sessions targeting IBD education, adherence, transition of responsibility, and self-advocacy. Participants complete pre- and post-assessment questionnaires assessing transition readiness (Transition Readiness Assessment Questionnaire) and program feasibility/acceptability. Results: Five adolescents and their parents have thus far completed the intervention and recruitment for our next cohort is underway. On average, transition readiness scores increased by 14.20 points from baseline to post-treatment (69.20 versus 83.40) and participants reported transitioning full responsibility for 2 additional self-management skills from parent to child by the end of the program. Parent rating of their own readiness, as well as their child's readiness, to transfer to adult care also increased ( P < 0.05). Regarding feasibility and acceptability, participants attended all study sessions and rated the convenience of the intervention as 5.4 out of 7 (very convenient). Participants found the group + individual format of the program helpful and likeable (both 6.4 out of 7—Strongly Agree). Finally, the helpfulness of the program in preparing patients to successfully transition to adult care was rated 5.8 out of 7 (a lot). Conclusions: Preliminary data suggest that STEP is efficacious in improving transition readiness in youth with IBD and their parents. Further, high session attendance and positive participant program ratings suggests that our intervention is both feasible and acceptable. Additional recruitment is underway to expand our study's sample size. Future research will examine generalizability by extending our transition program to other IBD centers in the country.